Pengaruh Customer Purchase Behavior, Word Of Mouth, dan Live Music Terhadap Keputusan Pembelian pada Generasi Z di Cafe Ampm Sidoarjo - Komala, Dewi Komala; Ardelia, Jaufa Putri; Hariasih, Misti (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to examine the influence of consumer purchasing behaviour, word of mouth (WoM), and live music performances on the purchasing decisions of Generation Z at Café AMPM Sidoarjo. A quantitative approach was employed, with the population consisting of Generation Z individuals in Sidoarjo Regency who have previously visited Café AMPM and are aged between 14 and 28 years. The sampling technique used was non-probability sampling with a purposive sampling method, involving 100 respondents. Data were collected through the distribution of questionnaires and measured using a Likert scale. For data processing and analysis, the study utilised the PLS-SEM method with the aid of SmartPLS software version 3.0. The findings indicate that consumer purchasing behaviour, word of mouth, and live music each have an influence on purchasing decisions at Café AMPM Sidoarjo.